2017
DOI: 10.1002/2017gl074263
|View full text |Cite
|
Sign up to set email alerts
|

Depth variations of 410 km and 660 km discontinuities in eastern North China Craton revealed by ambient noise interferometry

Abstract: Recent studies have demonstrated that body waves between pairs of stations can be successfully retrieved from ambient noise cross correlation at both regional and global scales, although surface waves are the dominant signals. However, it is still difficult to use these retrieved body wave signals to map lateral depth variations of main structural discontinuities or velocity contrasts because of its low signal‐to‐noise ratio (SNR). In this research, based on a dense seismic array in eastern North China Craton,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Receiver function analysis shows that the deconvolved Ps converted signals vary substantially and that some show multiple phases (Tian et al, 2016). A radically changed P660P and consistent P410P waves are also observed in published results conducted for the North China Craton, ~800 km southwest to our study region (Feng et al, 2017). The amplitude ratio of the P660P may be as high as 2, even in adjacent areas with ~40% overlap.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Receiver function analysis shows that the deconvolved Ps converted signals vary substantially and that some show multiple phases (Tian et al, 2016). A radically changed P660P and consistent P410P waves are also observed in published results conducted for the North China Craton, ~800 km southwest to our study region (Feng et al, 2017). The amplitude ratio of the P660P may be as high as 2, even in adjacent areas with ~40% overlap.…”
Section: Discussionsupporting
confidence: 91%
“…For comparison, we chose another area (Region I in Figure 1a) at a similar latitude but far from the hinge of the slab (Li et al, 2008) to avoid the potential complicated effects, such as the significant depression of the 660 or the effects caused by the slab interface of dipping portion. The two peaks appearing at ~100 and ~150 s in the stacked waveforms (Figure 2f) correspond to the body waves reflected at the 410‐ and 660‐km discontinuities, referred to as P410P and P660P, respectively, which have been detected and explored in recent studies (Feng et al, 2017; Poli, Campillo, et al, 2012). The slowness is around zero for both phases in the vespagrams calculated by Radon transformation (Schultz & Gu, 2013) (Figures 2d, S4b, S5b, and S6b), confirming the phases are reflected at the deep mantle discontinuities.…”
Section: Lower Mantle Reflections Extracted From Cross‐correlationmentioning
confidence: 78%
See 1 more Smart Citation
“…Claerbout (1968) showed that the reflectivity series of an acoustic media can be recovered by taking the autocorrelation of the normal‐incidence transmission response, a form of seismic interferometry, that was subsequently extended to elastic media and nonnormal incidence angles by Frasier (1970). Body‐wave reflection phases have been successfully extracted by cross‐correlating (Clayton, 2020; Feng et al, 2017; Lin & Tsai, 2013; Roux et al, 2005; Tkalčić & Pham, 2018; Zhan et al, 2010) and autocorrelating (Becker & Knapmeyer‐Endrun, 2018, 2019; Phạm & Tkalčić, 2018; Romero & Schimmel, 2018) the seismic wavefield. Most recent studies have focused on the extraction of Moho‐reflected phases (e.g., PmP and SmS) to determine crustal thickness by autocorrelating and stacking the ambient noise record (Gorbatov et al, 2013; Oren & Nowack, 2017; Tibuleac & von Seggern, 2012) or teleseismic earthquake data (Delph et al, 2019; Phạm & Tkalčić, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Zhou and Paulssen () analyzed borehole seismic noise data and extracted P and S waves from noise correlations. For larger scales, many other studies have retrieved and used body waves sampling the deeper subsurface from the cross correlation of seismic noise (Boué et al, ; Feng et al, ; Lin et al, ; Nishida, ; Poli et al, ).…”
Section: Introductionmentioning
confidence: 99%